Edvard Munch - Watkins, Peter; Saether, Odd Geir; Westby, Geir; Fraas, Gro; Allum, Eric (The Masters of Cinema Series, 2011)
Watkins' biography of the formative years of the pioneer Expressionist easily vindicates its running time. As Munch moves through his youth, quiet and alienated, we realise that he too was eluded by any lasting intimacy: a long, abortive affair with an older woman joins the ubiquitous ghosts of a childhood scarred by sickness and death. In the end it's the paintings which do Munch's talking for him, both directly and through the prefigurations and echoes in the film's set pieces, a fuzzed, mutely anguished procession of half-profiles and silently helpless groups with numb, naked eyes. It's a remarkable film. [www.timeout.com]